Students’ Experience in Learning English Vocabulary Through the Duolingo Application - Tamara, Susana Riska; Surtikanti, Monika Widyastuti (Universitas Pahlawan Tuanku Tambusai, 2025)
Vocabulary skills. While previous research has demonstrated the effectiveness of the Duolingo app in enhancing vocabulary acquisition, studies focusing on students’ learning experiences remain limited. A pre-research survey indicated that Duolingo is the most preferred application for independent vocabulary learning. This study explores the experiences of eighth-semester students in learning English vocabulary using Duolingo, focusing on cognitive, affective, and behavioral aspects. A qualitative case study method was employed, with data collected through questionnaires and semi-structured interviews involving students from the Faculty of Teacher Training and Education in a private university in West Kalimantan. The findings underscore the importance of integrating mobile technology as a standalone, enjoyable, and meaningful tool for vocabulary learning.